Dowry as Parental Motivation in Underage Marriage in Bogor, West Java - Iqbal Subhan Nugraha; Abdul Aziz; Ahmad Bahrul Hikam (Millati: Journal of Islamic Studies and Humanities, 2025)
The study focuses on dowry as parental motivation in underage marriage in Bogor, with the main question being how the misinterpretation of the concept of birrul walidain (filial piety to parents) drives the practice. The background of the issue shows that social and economic pressures often reinforce the erroneous interpretation of this concept, where young girls are forced into early marriage as a form of obedience to their parents. The position of this research is to critique the misinterpretation and offer a new perspective on the understanding of birrul walidain in the context of child rights protection. The method used is qualitative, involving in-depth interviews with five victims of early marriage. The relevant theories in this analysis are feminist theory and child rights, which are used to understand how social and patriarchal structures exploit girls through religious doctrine. The research findings indicate that family pressure and the incorrect application of birrul walidain have restricted the victims' freedom, leading to a loss of educational opportunities and personal freedom. The main conclusion of this study emphasizes the need for reform in religious and social education to improve societal understanding of balanced duty, thereby protecting children's rights from exploitation in the form of early marriage.